The Impact of the Requirement to Implement a Business Management System for Ship Agency Activities in Accordance with Circular Letter No. SE-DJPL 10 of 2025 on the Performance of Ship Agency Service Providers at Labuan Bajo Port - Nur Rohmah; Moh. Rafli Taufikurrahman; Torie Adhi Prasetianto (Return : Study of Management, Economic and Bussines, 2026)
The Ministry of Transportation issued Circular Letter of the Director General of Sea Transportation Number SE-DJPL 10 of 2025 concerning the obligation to fulfill Business Management System (SMU) document requirements for ship agency business actors. The purpose of this study is to determine the effectiveness of the Business Management System for ship agency business activities in accordance with Circular Letter Number SE-DJPL 10 of 2025 concerning the obligation to fulfill Business Management System (SMU) documents for ship agency business actors on the performance of ship agency service providers at the Port of Labuan Bajo, as well as to assess the impact of this obligation on their performance. This study employs a mixed-method approach, combining qualitative and quantitative methods through data collection techniques such as observation, interviews, documentation, and questionnaires. Data were analyzed using descriptive qualitative methods and SmartPLS, with triangulation of techniques and sources applied to enhance data validity. The results of this study indicate that the implementation of Business Management System (SMU) documents in accordance with Circular Letter Number SE-DJPL 10 of 2025 is effective in improving the performance of ship agency service providers at the Port of Labuan Bajo.